Toxicity Assessment of Buprofezin, Lufenuron, and Triflumuron to the Earthworm Aporrectodea caliginosa - Badawy, Mohamed E. I.; Kenawy, Anter; El-Aswad, Ahmed F. (International Journal of Zoology, 2013)
Earthworms are particularly important soil macroinvertebrates and are often used in assessing the general impact of pesticide pollution in soil. The present study was conducted in order to investigate the toxicity of three insect growth regulators (IGRs) buprofezin, lufenuron, and triflumuron, at different application rates and exposure times toward mature earthworms Aporrectodea caliginosa. The effects of these pesticides on the growth rate in relation to the activities of acetylcholinesterase (AChE) and glutathione S-transferase (GST) as biochemical indicators were evaluated to elucidate the mechanisms of action. Toxicity studies indicated that lufenuron was the most harmful pesticide to mature earthworms, followed in descending order by buprofezin and triflumuron. A reduction in growth rate in all pesticide-treated worms was dose-dependent over the 28-day exposure period, which was accompanied by a decrease in AChE and GST activities. Relationships between growth rate, AChE, and GST provided strong evidence for the involvement of pesticidal contamination in the biochemical changes in earthworms, which can be used as a bioindicator of soil contamination by pesticides.